The clinical and financial impact of introducing robotic‐assisted hysterectomy in a tertiary referral centre: A direct cost analysis of consecutive hysterectomies during a decade. Issue 1 (26th October 2021) - Dumont, Sander; Van Trappen, Philippe
Abstract: Background: Economic data and the clinical impact of introducing robotic‐assisted hysterectomy in a European setting are scarce with conflicting findings. Methods: In this retrospective cohort study, the cost and complication rate of the different approaches of hysterectomy are investigated, both benign and (pre)malignant indications were included. Results: 844 patients were included: 323 (38.3%) patients underwent robotic‐assisted hysterectomy (RAH), 317 (37.5%) total abdominal hysterectomy (TAH), and 204 (24.2%) total laparoscopic hysterectomy (TLH). TAH dropped from 67.2% to 25.5% of procedures, whilst RAH rose to 41.8% of cases. The total hospitalisation cost was for RAH €5208.39 (±€916.91), for TAH €5846.61 (±€4464.37) and for TLH €3790.06 (±€1267.05). The postoperative complication rate of TAH (9.1%) was significantly higher in comparison with TLH and RAH (5.4% and 3.1%, respectively, p  = 0.005). Conclusions: RAH has replaced TAH in most cases, especially for large uteri, early‐stage endometrial cancer and in selected endometriosis cases, resulting in reduced morbidity with lower hospitalisation costs. The indications for TLH remained, including menorrhagia, adenomyosis and persistent cervical dysplasia.